Food security and resilience of smallholder nature-positive farmers in Quezon, Philippines - LEILA D. LANDICHO; MARY ANNE G. ABADILLOS (Smujo International, 2025)
Abstract. Landicho LD, Abadillos MAG. 2025. Food security and resilience of smallholder nature-positive farmers in Quezon, Philippines. Asian J Agric 9: 712-726. The agriculture sector, particularly smallholder farmers, is highly vulnerable to climate and non-climate shocks, including extreme weather events, pest and disease outbreaks, and market price fluctuations. Promoting nature-positive food production, defined as the regenerative, non-depleting, and non-destructive use of natural resources, offers an important strategy to strengthen resilience and food security in farming communities. Agroforestry and organic agriculture are two farming systems that embody nature-positive principles by enhancing soil health, diversifying farm outputs, and minimizing dependence on synthetic inputs. Therefore, this study aims to assess the food security and resilience levels of smallholder farmers engaged in organic farming and agroforestry in Sariaya, Quezon, Philippines. This study assessed the food security and resilience of 159 agroforestry and 30 organic farmers in Sariaya, Quezon, Philippines, using household surveys, focus group discussions, and key informant interviews. Results showed that agroforestry and organic farmers achieved moderate to high levels of food security, with mean scores of 6.98 and 7.34, respectively, across the four dimensions of food availability, accessibility, stability, and utilization. However, financial and social capital remain the weakest links, limiting the overall resilience of smallholder systems. The study underscores that nature-positive approaches enhance both ecological integrity and household resilience. Strengthening institutional support, value-chain participation, and adaptive capacity can further sustain food systems under climate and economic stress.